Prejudice to The Inferior Races in Heart of Darkness Novella by Joseph Conrad - Irvani, Rodhy; Zamruddin, Mardliya Pratiwi; Alamsyah, Alamsyah (Fakultas Ilmu Budaya Universitas Mulawarman, 2024)
ABSTRACTThe word Prejudice or Prejudice lately can be defined as a preconceived thought or opinion about a person or a group solely based on the particular culture, ethnicity, gender, or religion that that person or group has. In literary works, the word prejudice or prejudice can be seen through a character or a group and even forms of prejudice can also be formed from within oneself. This study aims and discusses the forms of prejudice in Joseph Conrad's novella entitled Heart of Darkness. The purpose of this study is to identify the forms of prejudice formed by Marlow's character towards the African Congo ethnicity and to describe how the author characterizes these forms of prejudice in Marlow. This research focuses on the experience of prejudice or prejudice that is formed in Marlow's character.This research aims to identify the superior and inferior races in the novella Heart of Darkness. This study uses the Theory of Prejudice from Gordon Allport and Narrative Fiction from Rimmon Kennan to apply this research. In this literature, researcher used qualitative research methods. The results of this study indicated that antilocution (negro, and black people) several brands of stereotypes or prejudices given to African society by superior race (white people) and discrimination (exile, forced labor etc). The dominant data were found such as antilocution, and physical attack and the least found is Extermination. The highlights are in the Novel in Heart of Darknessthe forms of society that white people do prejudices to other races and still happen in the modern era right now. Keywords: Prejudice, Narrative, Superior, Inferior.